Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration - Ran Meixin; Deng Yaxin; Yan Jiaqi; Zhang Anan; Wei Ying; Li Xiaowen; He Haibing; Gou Jingxin; Yin Tian; Tang Xing; Kong Jun; Zhang Han; et al. (ELSEVIER SCIENCE SA, 2023)
The current treatment of wet age-related macular degeneration (wAMD) relies on monthly intravitreal or intravenously injection of vascular endothelial growth factor (VEGF) inhibitor or photodynamic (PDT) agents to inhibit choroidal neovascularization. However, traumatic local therapy and exogenous long-distance fundus drug delivery often lead to secondary eye damage, low treatment efficiency, and immunogenic inflammation. Herein, inspired by the natural neovascular targeting ability of endogenous low-density lipoproteins (LDL), a noninvasive bionic nano-eye-drop with enhanced ocular penetrability and lesion recognizability is developed for enabling the PDT treatment of wAMD. Verteporfin (VP) as a laser-induced PDT agent is protected inside the hydrophobic core of reconstituted LDL (rLDL) vectors. 5-carboxyfluorescein (FAM) conjugated ste-penetratin (PEN, a transmembrane peptide) is anchored on the surface of the rLDL carrier, which enabled the nanoparticles (PEN-rLDL-VP) to cross the blood-retina barrier to realizing visual therapy. Following instillation, PEN-rLDL-VP can effectively deliver VP into neovascular that overexpress LDL receptors, which can respond to laser-induced PDT. Only with a single dose of the eye-drop and laser-induced PDT, the VEGF and proinflammatory intercellular adhesion molecule-1 (ICAM-1) proteins are significantly down-regulated in vivo, which implicates the neovascular inhibition and inflammation alleviation. This study presents an attractive non-invasive strategy for the PDT of wAMD.